PENGARUH JEJARING SOSIAL ONLINE DAN STRESS MAHASISWA SEBAGAI PREDIKTOR KESEHATAN MENTAL DAN KECERDASAN EMOSIONAL DIKALANGAN FKIP UNJA - Ismayanti, Dea Try; Aulia, Aiza Miftahul; Yusuf, Muhammad (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2020)
The research aims to assess the impact of online social networking and student stress on their emotional and mental intelligence. The survey methodology employed in this study involved the distribution of questionnaires to collect data on respondents' characteristics, opinions, behaviors, and attitudes. To evaluate the research's analytical capacity, G Power was utilized to determine an adequate sample size, resulting in a total sample of 218 from a population of 8968, achieving a power of 0.95.Participants were requested to provide demographic information and rate their agreement with statements comprising 20 items derived from four constructs based on Tenzit Tyagi's work (2022). These constructs included online social networking (OSN) (5 items), student stress (SS) (5 items), mental health (MH) (5 items), and emotional intelligence (EI) (5 items). Mean scores were calculated to determine the levels of each variable. The mental health variable obtained the highest mean score (4.3), followed by emotional intelligence (mean 4.1), while student stress received the lowest mean score (mean 3.0).The research aims to identify and analyze the factors influencing online social networking and student stress as predictors of mental health and emotional intelligence among students in the Faculty of Education. The study examines four main variables: Online Social Networking (X1), Student Stress (X2), Mental Health (Y1), and Emotional Intelligence (Y2). The researcher has formulated six hypotheses to explore the impact of each variable on the research question. The ultimate objective is to gain a comprehensive understanding of how these factors interrelate and contribute to the overall well-being of students.